SPECTRAL INVESTIGATION OF FIELD BLUE STRAGGLERS - Chernyshova, I. V. (Одеські астрономічні публікації, 2017)
Field blue stragglers are counterparts of cluster blue stragglers. They were selected by Olsen in base of specific Stromgren indices among bright metal-deficient early F dwarfs. For some stars from this list, the high-resolution and high S/N CCD spectra were obtained. Synthetic spectrum technique was applied for the specification of rotational velocities and chemical composition of program stars. Special attention was payed on FBS with high rotation and broad shallow lines with aim of comparison of their chemical abundances and abundances of Λ Bootis type stars calculated with the same methodics. In general, 18 chemical elements were investigated. All metals show moderate deficiency. Most of the stars show normal abundance of sodium. With the exception of HD35863 the "normal" lithium abundance also was found in HD27523, HD45042 and HD88923. Main question was "What is FBS?" We discussed three hypothesis that could be applied for explanation of their nature: 1) they are really blue stragglers with prolonged evolution; 2) they are normal stars which were born in metal deficient medium; 3) they are an extension of Λ Boo stars towards lower temperature.